Saat Muṣḥaf al-Qur’ān menjadi Komoditas - Eva Nugraha (Refleksi: Jurnal Kajian Agama dan Filsafat, 2014)
Can the Qur’ān be traded? Is it allowable and lawful to do commodification of the holy scripture? In view of the fact that Muslim communities mostly require the Qur’ān, an effort for commercialization of it directly emerges, and this article concerns on such Qur’ānic commodification.The concern is completed from by analyzing theological, Islamic jurisprudence, and ethical perspectives, to the using of material for the Qur’ānic publication (environmental conscience) and the involvement of the state as well, by proposing standard of commodification.Keywords: Commodification of Qur’ān, standard of commodification, Muṣḥaf.DOI: 10.15408/ref.v13i6.998